Efficacy and Safety of Subcutaneous Golimumab in Methotrexate‐Naive Patients With Rheumatoid Arthritis: Five‐Year Results of a Randomized Clinical Trial. Issue 6 (26th May 2016) - Emery, Paul; Fleischmann, Roy M.; Strusberg, Ingrid; Durez, Patrick; Nash, Peter; Amante, Eric Jason B.; Churchill, Melvin; Park, Won; Pons‐Estel, Bernardo; Han, Chenglong; Gathany, Timothy A.; Xu, Stephen; et al.
Abstract : Objective: To evaluate the safety and efficacy of golimumab through 5 years in adults with active rheumatoid arthritis (RA) who had not previously received methotrexate (MTX). Methods: In the GO‐BEFORE study, 637 MTX‐naive adult patients with active RA were randomized (1:1:1:1) to placebo + MTX (group 1), golimumab 100 mg + placebo (group 2), golimumab 50 mg + MTX (group 3), or golimumab 100 mg + MTX (group 4). Inadequate responders in groups 1, 2, and 3 entered early escape at week 28 to golimumab 50 mg + MTX, golimumab 100 mg + MTX, or golimumab 100 mg + MTX, respectively; remaining patients in group 1 could cross over to golimumab 50 mg + MTX at week 52. Assessments included the American College of Rheumatology 20%/50%/70% improvement criteria (ACR20/50/70) response, the Disease Activity Score in 28 joints (DAS28) using C‐reactive protein (CRP) level, and the modified Sharp/van der Heijde score (SHS). Efficacy was analyzed using an intent‐to‐treat (ITT) analysis. Pharmacokinetics and immunogenicity were evaluated at selected visits. Results: A total of 422 patients completed golimumab treatment through week 256. At week 256, 72.8%, 54.6%, and 38.0% of all patients in the full ITT population (n = 637) had an ACR20/50/70 response, respectively; 84.1% had a good or moderate DAS28‐CRP response; and 72.7% had a clinically meaningful improvement in physical function. Radiographic progression was minimal in all treatment groups through week 256, and the overall mean change from baseline in SHS was 1.36. Serum trough golimumab concentrations were approximately dose proportional and maintained through week 256. Antibodies to golimumab occurred in 9.6% of patients through week 256. Infections were the most common type of adverse event (AE); 204 of 616 patients (33.1%) had ≥1 serious AE. Conclusion: Clinical efficacy with golimumab treatment was maintained through week 256 of the GO‐BEFORE trial of MTX‐naive RA patients. No unexpected AEs occurred; safety results through 5 years are consistent with earlier reports.